Analisis Pengaruh Ditutupnya Tempat Pembuangan Akhir (TPA) Piyungan Terhadap Keputusan Manajemen Keuangan UMKM - Novitasari, Novitasari; Utami, Kristiana Sri (Populer: Jurnal Penelitian Mahasiswa, 2024)
This research aims to investigate the process and impact of closing the Piyungan Final Disposal Site in the city of Yogyakarta to explore the economic impact. The research method used is a case study with a qualitative approach, including document analysis, in-depth interviews with relevant stakeholders, and field observations. The research results show that the closure of the landfill in Piyungan involves several crucial stages, including planning, technical implementation, and post-closure management. The effects of these landfill closures include causing significant changes in the local economy.